Prologue of the Poem in Works by Ibn Nabatah Al-Masri (deceased 768 h) - Yaseen Mohammed Al-Hamdani, Faris (Journal of College of Education, 2021)
Poetic prologue is the key to the poem and the threshold for the text. It is an artistic phenomenon that accompanied Arabic poetry from the ancient times up till the time being. The many forms and topics it has follow the Era and the poet's subjectivity. The research is an attempt to consider this tradition in Arabic poetry in the Middle Age through Al-Masri.It is the basis of the poetic text, represented in an aesthetic subjective formulation that is formulated by what the poet's senses get, and by the experiences and emotions he goes through. These result in aesthetic sensed poetic formulas satiated with emotions that are identified by the receiver, which shows the poet's ingenuity.Being a threshold, the poetic prologue is an important structural base that qualifies the reader to pass to the subject of the text, enabling for all interpretations. In addition to its denotational function, it has verbal and sensible values that make the reader engaged with the poet's imaginational atmosphere.The various poetic prologues are:• The impressive prologue.• The flirting prologue.• The wine prologue.• The complaint prologue.